Determination of the nutritional value of blocks with different inclusion percentages of Sambucus peruviana and Zea mays - Rodríguez-Molano, Carlos Eduardo; Pulido-Suárez, Néstor Julián (Universidad Pedagógica y Tecnológica de Colombia, 2018)
The low availability and quality of forages for bovines during critical periods (dry - rainy seasons) negatively impact the milk and meat production systems. This study aimed at evaluating the nutritional quality of nutritional blocks with different percentages of linden and corn inclusion. The plant material (leaves and stems) of corn and linden was collected with a vegetative period of 70 days since the emission. The material was dehydrated under greenhouse for five days, and subsequently the nutritional blocks of Sambucus peruviana and Zea mays were elaborated in two percentages of inclusion to determine their nutritive value (dry matter, crude fiber, ashes, and crude protein). All the variables were subjected to analysis of variance, Tukey test (5 %). Statistically significant differences were found (P <0.05) for the % of ash, fiber, and protein. Linden and corn, as multipurpose species, can be implemented under different landscape management tools and provide forage of a high quality.